Sinergi Ekosistem Keuangan Syariah: Konvergensi Perbankan, Pasar Modal, Asuransi, dan Lembaga Sosial Islam menuju Kemandirian Ekonomi Umat - Latief, Nur Fitry; Syafruddin, Muhammad (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Indonesia, as the country with the largest Muslim population in the world, possesses an enormous potential Islamic financial ecosystem that remains underutilised. This study analyses the synergy model among four main pillars of Islamic finance, Islamic banking, Islamic capital markets, takaful insurance, and Islamic social institutions (BAZNAS, LAZ, and productive waqf), in supporting the economic independence of the Muslim community. A systematic literature review was conducted, examining scientific publications, regulatory reports from OJK, Bank Indonesia, BAZNAS, and the Badan Wakaf Indonesia (BWI) for the period 2018–2024. Results indicate that Islamic banking assets grew at a CAGR of 13.2% (2021–2023), reaching IDR 898 trillion, while the Islamic capital market expanded 15.1% to IDR 1,748 trillion, and collected ZIS surged 38.3% to IDR 26.4 trillion. However, cross-sector integration remains weak, the Islamic financial inclusion index stands at only 24.3% for account access compared to 72.4% in conventional finance. This study formulates an Integrated Islamic Financial Ecosystem (IIFE) model that cohesively links commercial and social Islamic financial flows, supported by OJK and DSN-MUI regulatory frameworks.